Soluble TNF mediates amyloid-independent, diet-induced alterations to immune and neuronal functions in an Alzheimer’s disease mouse model - MacPherson, Kathryn P.; Eidson, Lori N.; Houser, Madelyn C.; Weiss, Blaine E.; Gollihue, Jenna L.; Herrick, Mary K.; de Sousa Rodrigues, Maria Elizabeth; Sniffen, Lindsey; Weekman, Erica M.; Hamilton, Adam M.; Kelly, Sean D.; Oliver, Danielle L.; et al. (Frontiers in Cellular Neuroscience, 2023)
Increasing evidence indicates that neurodegenerative diseases, including Alzheimer’s disease (AD), are a product of gene-by-environment interplay. The immune system is a major contributor mediating these interactions. Signaling between peripheral immune cells and those within the microvasculature and meninges of the central nervous system (CNS), at the blood-brain barrier, and in the gut likely plays an important role in AD. The cytokine tumor necrosis factor (TNF) is elevated in AD patients, regulates brain and gut barrier permeability, and is produced by central and peripheral immune cells. Our group previously reported that soluble TNF (sTNF) modulates cytokine and chemokine cascades that regulate peripheral immune cell traffic to the brain in young 5xFAD female mice, and in separate studies that a diet high in fat and sugar (HFHS) dysregulates signaling pathways that trigger sTNF-dependent immune and metabolic responses that can result in metabolic syndrome, which is a risk factor for AD. We hypothesized that sTNF is a key mediator of peripheral immune cell contributions to gene-by-environment interactions to AD-like pathology, metabolic dysfunction, and diet-induced gut dysbiosis. Here, we show that selective inhibition of sTNF signaling via the biologic XPro1595 modulates the effects of a HFHS diet in 5xFAD mice on peripheral and central immune profiles including CNS-associated CD8+ T cells, the composition of gut microbiota, and long-term potentiation deficits. A clinical trial in subjects at risk for AD due to genetic predisposition and underlying inflammation associated with peripheral inflammatory co-morbidities will be needed to investigate the extent to which these findings translate to the clinic.